Ultrastructural changes of immature bovine oocytes caused by freezing solution and freezing procedure - Thein, M.; Haron, Abd Wahid; Yusoff, Rosnina; Sianturi, Riasari Gail (Universiti Putra Malaysia Press, 2004)
Viability of frozen-thawed oocytes is very low with current techniques. This experiment was conducted to determine the ultrastructural changes caused by freezing solution and freezing procedure. Oocytes were recovered from ovaries obtained from abattoirs. The oocytes (n=30) were divided into 3 groups of 10 oocytes. The first group of oocytes acted as control. The oocytes in the second group were exposed to freezing solution for 10 min. whereas the oocytes in the third group were equilibrated in ethylene glycol-based freezing solution for 10 min and subsequently frozen. The frozen oocytes were thawed after 3 days. The ultrastucture of all oocytes were examined under transmission electron microscope. No significant changes in zona pellucida, perivitelline space, microvilli, mitochondria, cortical granules, vesicles, lipid droplets and germinal vesicles were observed in oocytes exposed to freezing solution. Abnormal changes in perivitelline space, microvilli and vesicle were observed in significantly increased percentage of oocytes that were subjected to the freezing procedure.